Conductive and injectable hyaluronic acid/gelatin/gold nanorod hydrogels for enhanced surgical translation and bioprinting. Issue 2 (14th August 2021) - Kiyotake, Emi A.; Thomas, Emily E.; Homburg, Hannah B.; Milton, Camille K.; Smitherman, Adam D.; Donahue, Nathan D.; Fung, Kar‐Ming; Wilhelm, Stefan; Martin, Michael D.; Detamore, Michael S.
Abstract: There is growing evidence indicating the need to combine the rehabilitation and regenerative medicine fields to maximize functional recovery after spinal cord injury (SCI), but there are limited methods to synergistically combine the fields. Conductive biomaterials may enable synergistic combination of biomaterials with electric stimulation (ES), which may enable direct ES of neurons to enhance axon regeneration and reorganization for better functional recovery; however, there are three major challenges in developing conductive biomaterials: (1) low conductivity of conductive composites, (2) many conductive components are cytotoxic, and (3) many conductive biomaterials are pre‐formed scaffolds and are not injectable. Pre‐formed, noninjectable scaffolds may hinder clinical translation in a surgical context for the most common contusion‐type of SCI. Alternatively, an injectable biomaterial, inspired by lessons from bioinks in the bioprinting field, may be more translational for contusion SCIs. Therefore, in the current study, a conductive hydrogel was developed by incorporating high aspect ratio citrate‐gold nanorods (GNRs) into a hyaluronic acid and gelatin hydrogel. To fabricate nontoxic citrate‐GNRs, a robust synthesis for high aspect ratio GNRs was combined with an indirect ligand exchange to exchange a cytotoxic surfactant for nontoxic citrate. For enhanced surgical placement, the hydrogel precursor solution (i.e., before crosslinking) was paste‐like, injectable/bioprintable, and fast‐crosslinking (i.e., 4 min). Finally, the crosslinked hydrogel supported the adhesion/viability of seeded rat neural stem cells in vitro. The current study developed and characterized a GNR conductive hydrogel/bioink that provided a refinable and translational platform for future synergistic combination with ES to improve functional recovery after SCI.